Identification and Mapping of Sigma-54 Promoters in Chlamydia trachomatis - Mathews, Sarah A. (American Society for Microbiology, 2000)
The first ς(54) promoters in Chlamydia trachomatis L2 were mapped upstream of hypothetical proteins CT652.1 and CT683. Comparative genomics indicated that these ς(54) promoters and potential upstream activation binding sites are conserved in orthologous C. trachomatis D, C. trachomatis mouse pneumonitis strain, and Chlamydia pneumoniae (CWL029 and AR39) genes.